MAKAM DAN INVASI MILITER Dl TARAKAN - Susanto, Nugroho Nur (Balai Arkeologi Kalimantan Selatan, 2009)
Up until today the general perspective of a grave is only a burial marker. In fact, a grave may be formed as a single burial, which accommodate an individual or communal for a group of people (cemetery). Archaeological research in regard tocemetery may provide information on the existence of an individual then, the arrival of a new community in a certain place or even a historical event such as military invasion, which indirectly indicate the occurrence of cultural acculturation. Cemeteries with graves showing particular characteristic and varieties of pattern are found in Tarakan. This article discusses the significance to study cemetery in order to· understand the historical occurrence, community dispersion and other important event occurred in Tarakan in the past.